The status of the nomina Trapelus savignyi Audouin, 1827 and Agama savignii Duméril & Bibron, 1837 and the valid nomen of the Savignys Agama (Sauria: Agamidae) - Wagner, Philipp; Crochet, Pierre-André (Zootaxa, 2009)
Herein we clarify the status of the nomen Trapelus savignyi Audouin, 1827 and Agama savignii Duméril & Bibron, 1837 by the designation of a lectotype of the former and a neotype of the latter species.